C-Arm Image-Based Surgical Path Planning Method for Distal Locking of Intramedullary Nails - Wei-En Hsu; Ching-Hsiao Yu; Chih-Ju Chang; Hung-Kang Wu; Tsong-Han Yu; Ching-Shiow Tseng (Applied Bionics and Biomechanics)
Due to the curvature of the bone marrow cavity, the intramedullary nail used in long bone fracture fixation can be deformed, causing displacement of the locking holes. In this study, an algorithm using only one C-arm image to determine the center positions and axial directions of locking holes was developed for drilling guidance. Based on conventional method that the axial direction of locking hole would be identified when locking hole contour is presented as a circle, the proposed method can locate the circle contour centroid by using one C-arm image including two elliptical contours. Then the two distal locking holes’ axial direction and centers would be determined. Three experiments were conducted to verify the performance of the proposed algorithm, which are (1) computer simulation, (2) use of real intramedullary nails, and (3) actual drilling test with the bone model. The experimental results showed that the average error of the axial direction and center position were 0.62 ± 0.6°, 0.73 ± 0.53 mm (simulation) and 3.16 ± 1.36°, 1.10 ± 0.50 mm (actual nail), respectively. The last ten drilling test sets were completed successfully (with an average duration of 48 seconds). Based on the experimental results, the proposed algorithm was feasible for clinic applications.